FINANCIAL STRATEGY OF SUSTAINABLE DEVELOPMENT OF INNOVATIVE ENTERPRISES - D. Voyko (Publishing House of the State University of Management, 2016)
The article focuses on the problems of developing financial strategy of sustainable development of innovative enterprises. The directions of financial strategy of innovative enterprises are determined in the article. Also the indicator of economic value added is proposed to evaluate the growth of the company's value and its effectiveness. The article also presents key performance indicators to evaluate the innovative activity of enterprises.